The Immunomodulation Potential of Exosomes in Tumor Microenvironment - Meng Wang; Bo Zhang (Journal of Immunology Research)
Exosomes are lipid bilayer particles that originated from almost all types of cells and play an important role in intercellular communication. Tumor-derived exosomes contain large amounts of noncoding RNA, DNA, and proteins, which can be transferred into recipient cells as functional components in exosomes. These exosomal functional constituents depend on the originating cells, and it has been proved that types and numbers of exosomal components differ in cancer patients and healthy individuals. This review summarizes the role of tumor-derived exosomes in immunomodulation and discusses the application of exosomes in immunotherapy in cancers. Overall, exosomes isolated from cancer cells are turned out to promote immune evasion and interfere with immune responses in tumors through inducing apoptosis of CD8+ T cells, facilitating generation of Tregs, suppressing natural killer (NK) cell cytotoxicity, inhibiting maturation and differentiation of monocyte, and enhancing suppressive function of myeloid-derived suppressor cells (MDSCs). Mechanistically, exosomal functional components play a significant role in the immunomodulation in cancers. Moreover, based on the existing studies, exosomes could potentially serve as therapeutic delivery vehicles, noninvasive biomarkers, and immunotherapeutic vaccines for various types of cancers.